A Pelatihan Mitigasi Bencana dari Aspek Geologi dan Perilaku Pada Masyarakat Desa Adat Senaru, Kecamatan Bayan Kabupaten Lombok Utara - Yunianti, Sri Rahmi; Ardi Yuniarman; Rasyid Ridha; Agus Kurniawan (LOSARI DIGITAL, 2025)
Senaru Traditional Village is one of the cultural sites in the Rinjani-Lombok Geopark Area located in Bayan District. Senaru Traditional Village has a geographical position and geological conditions that are quite vulnerable to disasters. In addition, this village has local wisdom values and strong socio-cultural structures, which influence how the community responds and faces disasters. Therefore, the purpose of this community service activity is to conduct effective disaster mitigation training by considering geological aspects and aspects of the behavior and culture of the local community to understand the geological characteristics of the area and identify behavioral aspects in disaster mitigation. Participants in this activity around 31 people involving figures from the Senaru Village Indigenous Community, including Bayan Traditional Leaders, Indigenous Youth, Bayan Traditional School, the Rinjani-Lombok Geopark Management Agency, the Rinjani Geopark Youth Forum, Literacy and Culture Activists, Geotourism Guides, and the public. The method in this activity was a partcipatory through Focus Group Discussion (FGD) with a holistic and in-depth approach to the geological conditions and community behavior in disaster mitigation. The results showed that the community understood the importance of identifying geological conditions in determining disaster mitigation, and they agreed that there must be a disaster-resilient community that will establish evacuation routes and assembly points in Senaru Village.